Edukasi Pencegahan Anemia pada Remaja Putri Dengan Mengkonsumsi Kurma di SMK Kesehatan Baiturrahim Kota Jambi - Julaecha Julaecha; Laida Sanilpa Tiwi; Fatihatul Hayati; Ajeng Galuh Wuryandari (Jurnal Abdimas Kesehatan (JAK), 2023)
Anemia is the impact of nutritional problems on young women which affect the decrease in concentration and learning achievement. The prevalence of anemia among adolescents in Indonesia is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. This is influenced by habits and nutritional intake that is not optimal and lack of physical activity. It is necessary to prevent anemia considering the long-term impact of young women is the nation's next generation which will determine the next generation. Dates contain iron which plays a very important role in the formation of red blood cells, the iron content in 100 grams of dates is around 280 calories and various nutrients, one of which is 1 mg of iron. This community service aims to increase youth knowledge about anemia, prevention of anemia, the content and benefits of dates. This community service method is lecture and discussion. The media used for counseling are leaflets, PPT. to measure knowledge (pre-test and post-test) with a questionnaire. held at the Baiturrahim Health Vocational School, Jambi City, in January 2022, attended by 35 participants. The result of this community service is an increase in students' knowledge about anemia, prevention, content and benefits of dates. It is hoped that young women can apply clean and healthy living behaviors as an effort to prevent anemia